Al-Tahlīl al-Wasfī ‘an Mawād Mahārah al-Kalām fī Kitāb Durūs al-Lughah al-ʿArabiyyah li Manhaj 2013 - Ali Nasuha; Elsa Sepputri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The background of this research is because there is a discrepancy between the arrangement of kalam material in Class 1 Arabic Language Books at Madrasah Ibtidaiyah and the standard presentation of kalam material by Abdurrahman bin Ibrahim al-Fauzan. Therefore, this study aims to see the suitability of the preparation of kalam material in Class 1 Arabic Language Books at Madrasah Ibtidaiyah with Abdurrahman bin Ibrahim al-Fauzan's standard of presentation of kalam material. The research methodology to descriptive Content Analysis. From the results of the analysis of the kalam material in the Class 1 Arabic Book of Madrasah Ibtidaiyah, the result is that the kalam material in the Arabic book is in accordance with the standard of presentation of the kalam material, but still requires improvement in certain parts, and the content of the existing material. appropriate to the level of student needs. If the writing of this book refers to the standards that have been prepared by Ibrahim Fauzan, then this book will be easy for students to understand and easy to apply.تعود خلفية هذا البحث إلى وجود تناقض بين ترتيب مادة الكلام في كتب اللغة العربية للصف الأول في مدرسة الابتداية والعرض القياسي لمادة الكلام لعبد الرحمن بن إبراهيم الفوزان. لذلك، تهدف هذه الدراسة إلى معرفة مدى ملاءمة تحضير مادة الكلام في كتب اللغة العربية للصف الأول بالمدرسة الابتداية مع معيار عبد الرحمن بن إبراهيم الفوزان لمواد الكلام. منهج البحث الوصفي لتحليل المحتوى. من نتائج تحليل مادة الكلام في الكتاب العربي للصف الأول من المدرسة الإبتدائية، كانت النتيجة أن مادة الكلام في الكتاب العربي تتوافق مع معيار تقديم مادة الكلام، ولكنها لا تزال بحاجة إلى تحسين في بعض الأجزاء ومحتوى المواد الموجودة. تتناسب مع مستوى احتياجات الطلاب. يأمل الباحث أن تكون كتاب اللغة العربية للصف الأول الابتدائي للصف الأول الابتدائية كمالاً، بحيث تصبح اللغة العربية يحبون الطلاب.